Foot and mouth disease (FMD)-2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Julius Chulu, Principal Animal Health Officer at Lilongwe Agricultural Development Division in Malawi.